The effect of biochemical oxidation on the hydrometallurgical production of copper - Koizhanova, Aigul; Magomedov, David; Abdyldayev, Nurgali; Yerdenova, Maria; Bakrayeva, Akbota (Universitas Negeri Padang, 2023)
The article presents the results of the use of the biochemical leaching method for copper-bearing non-commercial ore in a full hydrometallurgical cycle. The object of the study was the average copper-bearing ore of the Satbayev deposit, with an initial copper content of 0.26%. The experimental part of the full hydrometallurgical cycle included percolation leaching, extraction, and re-extraction tests, as well as electrodeposition tests and the production of finished cathode copper. Two variants of percolation leaching were performed as a comparison: a standard method using only sulfuric acid and a preliminary bacterial oxidation method for mineral raw materials with an adapted bacterial strain, Acidithiobacillus ferrooxidans. Percolation leaching experiments showed a significant reduction in sulfuric acid consumption when preliminary bacterial oxidation was used. Upon reaching the level of copper extraction from the ore of 86–87%, the final consumption of sulfuric acid for the standard leaching method was 15.5 kg per ton, while 9.4 kg per ton was required for the biochemical method. The productive solution obtained in the biochemical leaching process showed full suitability for all technological stages of hydrometallurgical copper production.